No benefit of HIF prolyl hydroxylase inhibition for hypertensive renal damage in renovascular hypertensive rats - Hartner, Andrea; Dambietz, Thomas; Cordasic, Nada; Willam, Carsten; Burzlaff, Nicolai; Brötsch, Martin; Daniel, Christoph; Schiffer, Mario; Amann, Kerstin; Veelken, Roland; Schley, Gunnar; Hilgers, Karl F. (Frontiers in Physiology, 2023)
Introduction: We previously reported that malignant hypertension is associated with impaired capillary density of target organs. Here, we tested the hypothesis that stabilization of hypoxia-inducible factor (HIF) in a modified “preconditioning” approach prevents the development of malignant hypertension. To stabilize HIF, we employed pharmacological inhibition of HIF prolyl hydroxylases (PHD), enzymes that profoundly affect HIF metabolism. Methods: Two-kidney, one-clip renovascular hypertension (2K1C) was induced in rats; controls were sham operated. 2K1C rats received either intermittent injections of the PHD inhibitor ICA (2-(1-chloro-4-hydroxyisoquinoline-3-carboxamido) acetate) or placebo. Thirty-five days after clipping, the frequency of malignant hypertension was assessed (based on weight loss and the occurrence of characteristic vascular lesions). In addition, kidney injury was compared between all ICA treated versus all placebo treated 2K1C, regardless of the occurrence of malignant hypertension. HIF stabilization was evaluated by immunohistochemistry, and HIF target gene expression by RT-PCR. Results: Blood pressure was elevated to the same degree in ICA- and placebo-treated 2K1C compared to control rats. ICA treatment did not affect the frequency of malignant hypertension or the extent of kidney tissue fibrosis, inflammation, or capillary density. There was a trend towards higher mortality and worse kidney function in ICA-treated 2K1C rats. ICA increased the number of HIF-1α-positive renal tubular cell nuclei and induced several HIF-1 target genes. In contrast, expression of HIF-2α protein as well as HIF-2 target genes were markedly enhanced by 2K1C hypertension, irrespective of ICA treatment. Discussion: We conclude that intermittent PHD inhibition did not ameliorate severe renovascular hypertension in rats. We speculate that the unexpected strong renal accumulation of HIF-2α in renovascular hypertension, which could not be further augmented by ICA, may contribute to the lack of a benefit from PHD inhibition.